Kajian Potensi Etil Asetat Ekstrak Daun Andaliman : Total Fenol Flavonoid dan Aktivitas Uji Antioksidan - Muhtamilatur Rahma; Roy Indrianto Bangar; Muhammad Yunus (Yayasan Literasi Sains Indonesia, 2026)
Andaliman leaves (Zanthoxylum acanthopodium DC.) are a traditional plant native to North Sumatra with potential as a natural antioxidant source due to their phenolic and flavonoid compounds. This study aimed to evaluate the antioxidant potential of the ethyl acetate extract of andaliman leaves based on total phenolic content, total flavonoid content, and antioxidant activity. Extraction was carried out using the maceration method with ethyl acetate as the solvent. Total flavonoid content was determined using the AlCl₃ method with quercetin as the standard, while total phenolic content was analyzed using the Folin– Ciocalteu method with gallic acid as the standard. Antioxidant activity was evaluated using the DPPH radical scavenging assay. The results showed that the ethyl acetate extract of andaliman leaves contained 73.40 mg QE/g extract of total flavonoids (7.3%) and 148.48 mg GAE/g extract of total phenolics. The antioxidant activity test yielded an IC₅₀ value of 4,2485 µg/mL, indicating that the extract exhibits very strong antioxidant activity. The high levels of phenolic and flavonoid compounds are believed to play an important role in the radical scavenging activity observed. Based on these findings, it can be concluded that the ethyl acetate extract of andaliman leaves has strong potential to be developed as a natural antioxidant source for applications in the pharmaceutical and health fields.